The Pharmacist's Role in CAR-T Cell Therapy: From Protocol Development to Toxicity Reduction - Alghamdi, Abdulrahman Atiah; Almalki, Naif Ali; Althubyani, Fahad Mosakin; Alshamrani, Saleh Awadh; Alsharif, Manal Abdulaziz; Alamri, Eisi Menwer (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> CAR-T cell therapy is cutting-edge immunotherapy for hematologic malignancies, and the pharmacist has a crucial role to play in its safe delivery. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: Through this review, the pharmacist's role in CAR-T therapy, ranging from protocol development to toxicity management, is evaluated with consideration of real-world evidence and the future direction. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A Systematic literature review was conducted on PubMed, Embase, and Web of Science using searches for studies between 2017–2025. Relevance to pharmacist roles in CAR-T therapy informed study selection, synthesizing data on protocol management, product handling, and toxicity mitigation. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pharmacists enable regulatory compliance, manage product logistics, and guide toxicity interventions, reducing adverse events by up to 40% in some settings. Case studies illustrate outpatient care (85% ambulatory care) and tocilizumab early start (90% severe CRS prevention). Complications are supply chain interruption and limited specialist roles (20% of centers). <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pharmacists are the key to the success of CAR-T therapy, improving safety and outcomes. Dedicated positions and standardized training would be necessary to cope with emerging challenges, especially in outpatient and solid tumor settings.